Apparent Lack of BRAFV600E Derived HLA Class I Presented Neoantigens Hampers Neoplastic Cell Targeting by CD8+ T Cells in Langerhans Cell Histiocytosis - Kemps, Paul G.; Zondag, Timo C.; Steenwijk, Eline C.; Andriessen, Quirine; Borst, Jelske; Vloemans, Sandra; Roelen, Dave L.; Voortman, Lenard M.; Verdijk, Robert M.; van Noesel, Carel J. M.; Cleven, Arjen H. G.; Hawkins, Cynthia; et al. (Frontiers in Immunology, 2020)
Langerhans Cell Histiocytosis (LCH) is a neoplastic disorder of hematopoietic origin characterized by inflammatory lesions containing clonal histiocytes (LCH-cells) intermixed with various immune cells, including T cells. In 50-60% of LCH-patients, the somatic BRAFV600E driver mutation, which is common in many cancers, is detected in these LCH-cells in an otherwise quiet genomic landscape. Nonsynonymous mutations like BRAFV600E can be a source of neoantigens capable of eliciting effective antitumor CD8+ T cell responses. This requires neopeptides to be stably presented by Human Leukocyte Antigen (HLA) class I molecules and sufficient numbers of CD8+ T cells at tumor sites. Here, we demonstrate substantial heterogeneity in CD8+ T cell density in n=101 LCH-lesions, with BRAFV600E mutated lesions displaying significantly lower CD8+ T cell:CD1a+ LCH-cell ratios (p=0.01) than BRAF wildtype lesions. Because LCH-lesional CD8+ T cell density had no significant impact on event-free survival, we investigated whether the intracellularly expressed BRAFV600E protein is degraded into neopeptides that are naturally processed and presented by cell surface HLA class I molecules. Epitope prediction tools revealed a single HLA class I binding BRAFV600E derived neopeptide (KIGDFGLATEK), which indeed displayed strong to intermediate binding capacity to HLA-A*03:01 and HLA-A*11:01 in an in vitro peptide-HLA binding assay. Mass spectrometry-based targeted peptidomics was used to investigate the presence of this neopeptide in HLA class I presented peptides isolated from several BRAFV600E expressing cell lines with various HLA genotypes. While the HLA-A*02:01 binding BRAF wildtype peptide KIGDFGLATV was traced in peptides isolated from all five cell lines expressing this HLA subtype, KIGDFGLATEK was not detected in the HLA class I peptidomes of two distinct BRAFV600E transduced cell lines with confirmed expression of HLA-A*03:01 or HLA-A*11:01. These data indicate that the in silico predicted HLA class I binding and proteasome-generated neopeptides derived from the BRAFV600E protein are not presented by HLA class I molecules. Given that the BRAFV600E mutation is highly prevalent in chemotherapy refractory LCH-patients who may qualify for immunotherapy, this study therefore questions the efficacy of immune checkpoint inhibitor therapy in LCH.